Peran Masyarakat Lokal dalam Pengembangan Destinasi Glamping di Kota Malang, Jawa Timur - Muhammad Irfan (Jurnal of Management and Social Sciences, 2024)
The same busy and troubled day-to-day problems fill people. Nature with varied topography like hilly areas, coasts, valleys, and others creates beautiful areas. One region that has topographic diversity exists in poor cities.One of the activities that can enjoy nature directly is camping. Not everybody can do camping activities because of the difficult terrain to access. Therefore, there is a glamping that is a luxurious and practical camping activity as a solution. Glamping can be combined with a resort that is a tourist destination equipped with accommodation facilities and produces a glamping resort that offers comfort to visitors to stay outdoors. The method used is a case study method based on existing data, the objective of planning is to design a tourist area without having to damage nature, adapting to the conditions of the site already existing, and easily passable. The results of planning are tourist areas that can be easily reached consisting of several masses of buildings placed on a particular area as facilities from areas such as glamping lodging placed in the back of the area and outbounds placed scattered following the shape of the contours of the region.